2014
DOI: 10.1093/aob/mcu132
|View full text |Cite
|
Sign up to set email alerts
|

AGO1 controls arabidopsis inflorescence architecture possibly by regulating TFL1 expression

Abstract: The results identify AGO1 as a repressor of TFL1 expression. Moreover, they reveal a novel role for AGO1 in inflorescence development, controlling the production of coflorescences. AGO1 seems to play this role through regulating TFL1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
16
0
2
Order By: Relevance
“…In the F3 and F4 progeny of the latter plants, a 3:1 (Hyg r :Hyg s ) segregation was observed, confirming that they were homozygous for ago1-52 but hemizygous for amiR-MAS2.1. The phenotype of the ago1-52/ago1-52; amiR-MAS2.1/amiR-MAS2.1 lethal seedlings resembled that of plants homozygous for null alleles of AGO1, whereas the ago1-52/ago1-52; amiR-MAS2.1 plants were very similar to those homozygous for the ago1-103 mutation, a very strong but viable allele of AGO1 (Fernández-Nohales et al, 2014).…”
Section: Amir-mas21 Increases the Severity Of The Mutant Phenotype Omentioning
confidence: 93%
“…In the F3 and F4 progeny of the latter plants, a 3:1 (Hyg r :Hyg s ) segregation was observed, confirming that they were homozygous for ago1-52 but hemizygous for amiR-MAS2.1. The phenotype of the ago1-52/ago1-52; amiR-MAS2.1/amiR-MAS2.1 lethal seedlings resembled that of plants homozygous for null alleles of AGO1, whereas the ago1-52/ago1-52; amiR-MAS2.1 plants were very similar to those homozygous for the ago1-103 mutation, a very strong but viable allele of AGO1 (Fernández-Nohales et al, 2014).…”
Section: Amir-mas21 Increases the Severity Of The Mutant Phenotype Omentioning
confidence: 93%
“…Further analysis revealed that 37 MADS-box transcription factors may perform important functions in cotton flower development, including 5 AP1, 6 AGL6, 3 SEP2, 2 SEP3, 2 SEP4, 3 AG, 4 AP3 and 4 PI (Additional file 1 : Table S3 and Fig. 6 c), which had been demonstrated to play pivotal roles in Arabidopsis floral induction and development [ 24 , 25 ]. KEGG pathway analysis showed that these differentially expressed genes were mainly involved in secondary metabolism, plant hormone signal transduction and starch and sucrose metabolism (Additional file 1 : Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…AGO1 stabilized miR168 posttranscriptional and the transcripts of AGO1 were regulated by miR168, which played an important role in plant development [ 29 ]. AGO1 and AGO10 interacted with miR172 and miR165/166 regulate the SAM and floral meristems development through targeting APETALA2 (AP2) and type III homeodomain-leucine zipper (HD-Zip) genes, respectively [ 28 , 30 , 31 , 32 ]. Cells in the SAM whether differentiated or not were regulated by HD-Zip transcription factors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%